Drug-Induced Autoimmune Hepatitis From Hydralazine Leading to Acute Liver Failure and Liver Transplantation. Issue 10 (October 2019) - Grewal, Jasleen; Doan, Angela; Hong, Annie S.; Amin, Arpit; Scapa, Jason V.; Hanna, Ramy; Durazo, Francisco; Yanny, Beshoy
Abstract : ABSTRACT: We describe a woman with no previous liver disease who developed drug-induced autoimmune hepatitis from hydralazine prescribed to her for hypertension. Despite the discontinuation of the medication, she developed acute liver failure and subsequently underwent successful liver transplantation. She survived and had a good clinical outcome.